Computational method for determining the mechanical tension in a self-anchored suspension bridge during construction and its engineering application. Issue 5 (3rd July 2017) - Lu, Pengzhen; Shao, Hua; Cheng, Jian Ting
Abstract : Purpose: The purpose of this paper is to develop a simplified optimization calculation method to assess cable force of self-anchored suspension bridge based on optimization theories. Design/methodology/approach: A simplified analysis method construction using Matlab is developed, which is then compared with the optimization method that considers the main cable's geometric nonlinearity with software ANSYS in an actual bridge calculation. Findings: This contrast proves the weak coherence and the adjacently interaction theory unreasonable and its limitation. Originality/value: This paper analyzes the calculation method to assess cable force of a self-anchored suspension bridge and its application effect.